Compatibility of insecticides with rice resistance to planthoppers as influenced by the timing and frequency of applications - Horgan, Finbarr G.; Peñalver-Cruz, Ainara (MDPI, 2022)
The brown planthopper, Nilaparvata lugens (Stål)(BPH) is a pest of rice in Asia. We examined the effects of seven insecticides combined with host resistance against BPH. In a screenhouse environment, we treated BPH-infested and non-infested resistant (IR62) and susceptible (IR64) rice with buprofezin, carbofuran, cartap hydrochloride, cypermethrin, deltamethrin, fipronil, or thiamethoxam + chlorantraniliprole. In one experiment, plants received one, two or three applications. In a second experiment, plants received one early or late insecticide application. Carbofuran and fipronil reduced planthopper biomass densities but resistance did not contribute to these effects (i.e., resistance was redundant). Single applications of cartap hydrochloride (at 20 or 50 days after sowing (DAS)), cypermethrin (20 DAS), or buprofezin (50 DAS) reduced BPH biomass densities on IR62 (i.e., synergies); other insecticides and application times, and multiple applications of all insecticides did not reduce BPH biomass densities on IR62 more than on IR64 (i.e., either resistance or insecticides were redundant). Deltamethrin (three applications) was antagonistic to resistance, but host resistance tended to buffer against the negative effects of single deltamethrin applications. Yields of infested IR62 were not statistically improved by insecticide applications. Late applications reduced yields of non-infested rice. We discuss how prophylactic insecticide applications could destabilize BPH populations and reduce the productivity and profitability of resistant rice.